2002
DOI: 10.1046/j.1365-2478.2002.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep structure of the northeastern margin of the Parnaiba Basin, Brazil, from magnetotelluric imaging

Abstract: The magnetotelluric (MT) method has been applied to the determination of the deep resistivity structure of the northeastern margin of the Parnaiba Basin. Transient electromagnetic (TEM) and MT data were collected in early 1999 along a 95 km long N–S line, extending from the coast across the projected subcrop position of a discontinuous fault found to the west of the study area that is believed to be a possible basin‐bounding fault. The MT data were processed to yield the TE‐ and TM‐mode responses and then corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…We then corrected all the dual‐mode AMT and LMT apparent resistivity sounding curves for static‐shift arising from near‐surface heterogeneities using the dual‐configuration TEM data [e.g., Mohamed et al , 2002; Sakkas et al , 2002; Meju et al , 2003] as in the examples shown in Figure 3 (see Table 1 for all the correction factors), thus providing a stringent control of the level of MT apparent resistivities that is necessary for improved estimation of subsurface resistivity and interface depths. We recognize that this surface‐consistent static‐shift correction approach (weathering correction, sensu stricto) may not account for static‐shift arising from deeper small‐size 3‐D heterogeneities [e.g., Bahr et al , 2000].…”
Section: Reanalysis Of Broadband Mt Data From Southern Kenyamentioning
confidence: 99%
“…We then corrected all the dual‐mode AMT and LMT apparent resistivity sounding curves for static‐shift arising from near‐surface heterogeneities using the dual‐configuration TEM data [e.g., Mohamed et al , 2002; Sakkas et al , 2002; Meju et al , 2003] as in the examples shown in Figure 3 (see Table 1 for all the correction factors), thus providing a stringent control of the level of MT apparent resistivities that is necessary for improved estimation of subsurface resistivity and interface depths. We recognize that this surface‐consistent static‐shift correction approach (weathering correction, sensu stricto) may not account for static‐shift arising from deeper small‐size 3‐D heterogeneities [e.g., Bahr et al , 2000].…”
Section: Reanalysis Of Broadband Mt Data From Southern Kenyamentioning
confidence: 99%
“…We have reanalyzed some available field data comprising high‐quality collocated tensor MT and multigeometry TEM soundings along individual survey lines in different geological settings [ Meju , 1996; Danladi , 1997; Simpson et al , 1997; Meju et al , 1999; Mohamed et al , 2002; Sakkas et al , 2002] to gain some practical insight into possible geological and statistical constraints on static shifts and hence place the inverse problem within a robust geological framework. We sought to understand the pattern of variation of overburden resistivity and static shift with lithology at different spatial scales using soundings for which the station intervals ranged from 1 km (in a small‐scale survey) to 20 km (in a large‐scale regional survey).…”
Section: Introductionmentioning
confidence: 99%
“…) and groundwater investigation (Sandberg ; Mohamed et al . ). In space constrained areas such as undulating mountains and coal mine fields, small‐loop instruments are preferred for TEM exploration since large loops are difficult to deploy.…”
Section: Introductionmentioning
confidence: 97%